Uyghur Poems - Elkun, Aziz Isa (New York : Alfred A. Knopf, a division of Penguin Random House LLC, 2023)
This unprecedented collection of poems spans the rich two-thousand-year cultural legacy of the Uyghur people of Central Asia. The Uyghurs have a long and glorious history of poetry, dating from the oral epics of the second century BCE through the elegant love poetry of the medieval period and up to the present moment -- and much of it has never before been translated into English. Uyghur poetry reflects the magnificent natural landscapes at the heart of the Silk Road region, with its endless steppes, soaring mountain ranges, and vast deserts, as well as its turbulent history. Turkic, Sufi, and Persian influences have shaped the poetic tradition over the centuries, and more recently the modernism of the twentieth century left its mark as well. In the face of the systematic persecution of the Uyghurs in China today, which has driven many of their poets into exile, Uyghur Poems is not only a remarkable one-volume tour of an ancient and vibrant poetic tradition but also a vital witness to a threatened culture.
Keywords: Uighur poetry